Identifiability of electrical and heat transfer parameters using coupled boundary measurements. (16th January 2017) - Chang, Yifan
Abstract: In this paper, we show that a hybrid method using coupled boundary measurements can determine anisotropic electrical conductivity, anisotropic thermal conductivity, and the product of heat capacity and heat density within a bounded domain on the plane uniquely up to a boundary-fixing diffeomorphism.